2016
DOI: 10.1002/stc.1882
|View full text |Cite
|
Sign up to set email alerts
|

Improving performance of a super tall building using a new eddy-current tuned mass damper

Abstract: SUMMARYTwo kinds of methods have been primarily used to improve the vibration performance of high-rise buildings. One approach is to enhance the structural lateral stiffness, which may increase the component size and inefficiently use material. The other approach is to employ vibration control devices, such as tuned mass dampers (TMDs), tuned liquid dampers (TLD) and other supplemental damping devices. This latter approach has proved to be quite economical and efficient, and as such, increasingly used in pract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
67
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(68 citation statements)
references
References 20 publications
1
67
0
Order By: Relevance
“…In addition, the modal frequencies of the first five modes were also identified and labelled in Figure . Noticeably, the frequencies of 0.110, 0.317, and 0.659 Hz are approximately close to those of the analytical results (Lu et al., ) of 0.110, 0.319, and 0.687 Hz, respectively.…”
Section: Real‐world Case Studysupporting
confidence: 87%
See 2 more Smart Citations
“…In addition, the modal frequencies of the first five modes were also identified and labelled in Figure . Noticeably, the frequencies of 0.110, 0.317, and 0.659 Hz are approximately close to those of the analytical results (Lu et al., ) of 0.110, 0.319, and 0.687 Hz, respectively.…”
Section: Real‐world Case Studysupporting
confidence: 87%
“…From the viewpoint of engineering practice, the real‐world EC‐TMD device with complicated configurations is one step forward to the scaled prototype previously used in the lab. The conceptual design, a brief description of the working principle of the EC‐TMD, and the numerically simulated vibration suppression performance of the EC‐TMD subjected to both earthquake and wind excitations can be referenced in a previous work by the authors (Lu et al., ).…”
Section: Real‐world Case Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The Lorentz force in the conductive plate will hinder the relative motion, and the vibration energy is dissipated by the heat of the conductive plate. Lu et al [18] studied the improving performance of a super tall building using a new eddy current tuned mass damper (ECTMD). Bourquin et al [19] introduced the magnetically tuned mass dampers for optimal vibration damping of large structures.…”
Section: Introductionmentioning
confidence: 99%
“…Niu et al [43] applied an ECTMD on a bridge to suppress the wind-induced vibrations that occur in the bridge hangers. Lu et al [44] investigated the vibration suppression performance of an ECTMD in Shanghai Center Tower, and the experimental results showed that the acceleration resulting from wind-induced vibration was reduced by 45-60%.…”
Section: Introductionmentioning
confidence: 99%